1994
DOI: 10.1073/pnas.91.7.2669
|View full text |Cite
|
Sign up to set email alerts
|

The NodC protein of Azorhizobium caulinodans is an N-acetylglucosaminyltransferase.

Abstract: The symbiosis between Azorhizobium, Bradyrhizobium, or Rhizobium species and legumes results in nitrogen-fixing nodules. The first stage of this interaction leads to the activation of bacterial nodulation (nod) genes by plant flavonoids. The nod genes are involved in the production ofNod factors (1-6), which act as host-specific signals to trigger nodule formation (1,2,5,7,8). The backbone of all Nod factors consists of an N-acetylglucosamine oligosaccharide (three to five sugar residues) from which the acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
5

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(102 citation statements)
references
References 26 publications
3
89
0
5
Order By: Relevance
“…Chitooligomers of rhizobia are synthesized by the product of the nodC gene, which is known to be a Nacetylglucosaminyl transferase. This enzyme employs UDP-N-acetylglucosamine as substrate to lengthen the oligochitin chain [17][18][19][20]. It seems likely that the R. fredii enzyme is able to replace this intermediate with UDP-glucose, the normal substrate for the synthesis of [3-glucans [21].…”
Section: Discussionmentioning
confidence: 99%
“…Chitooligomers of rhizobia are synthesized by the product of the nodC gene, which is known to be a Nacetylglucosaminyl transferase. This enzyme employs UDP-N-acetylglucosamine as substrate to lengthen the oligochitin chain [17][18][19][20]. It seems likely that the R. fredii enzyme is able to replace this intermediate with UDP-glucose, the normal substrate for the synthesis of [3-glucans [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although GalNAc-capped chitobiose has previously been observed as a very minor antenna in N-glycans from the serine protease of pit viper venom (24), this is the first report of chito-oligomers in a eukaryotic glycoprotein. The closest homology to these structures in nature are the Nod factors, which are signal molecules produced by Azorhizobium, Bradyrhizobium, and Rhizobium species that trigger nodule formation in leguminous plants (25). Recently it has been shown that Nod-like molecules are FIG.…”
Section: Characterization Of Filarial Nematode N-glycans 20958mentioning
confidence: 99%
“…Bacterial strains and plasmids are listed in Table 1, which is published as supporting information on the PNAS web site. A. caulinodans strains were grown overnight at 37°C in yeast extract broth medium (20).…”
Section: Methodsmentioning
confidence: 99%